Applications of Mixed Reality Technology in Orthopedics Surgery: A Pilot Study - Lu, Lin; Wang, Honglin; Liu, Pengran; Liu, Rong; Zhang, Jiayao; Xie, Yi; Liu, Songxiang; Huo, Tongtong; Xie, Mao; Wu, Xinghuo; Ye, Zhewei (Frontiers in Bioengineering and Biotechnology, 2022)
Objective: The aim of this study was to explore the potential of mixed reality(MR) technology in the visualization of orthopedic surgery. Background: Several advantages of MR holograms in surgery have been demonstrated including: 1) real-time sharing of 3D lesion holograms among surgeons, 2) depth fitting between real and virtual worlds, and 3) real-time interaction. Methods: The visualization system with MR technology are used in orthopedic surgery. The system is composed of a 3D imaging workstation, a cloud platform and an MR space station. An intelligent segmentation algorithm is run on the 3D imaging workstation to create a 3D model of the lesion and its surrounding anatomy with zooming and rotation effects, realizing efficient 3D reconstruction of CT and MRI data. Following each procedure, nine surgeons completed a Likert-scale questionnaire on communication and understanding, spatial awareness and effectiveness of MR technonlogy use. Besides that, the National Aeronautics and Space Administration Task Load Index (NASA-TLX) is also used to evaluate the workload of MR hologram support. Results: (1) Holograms provide an intuitive communication tool among doctors and between doctors and patients; (2) During surgical operations, a full lesion hologram can be obtained and blended in real time with a patient's virtual 3D digital model in order to give surgeons superior visual guidance through novel high-dimensional ‘perspectives’ of the surgical area; (3) Hologram-based magnetic navigation improves the screw placement accuracy and safety in orthopaedic surgical operations; (4) The combination of mixed reality cloud platform and telemedicine system based on 5G provides a new technology platform for telesurgery collaboration. Analysis of the Likert-scale questionnaire showed that MR added significant value to the understanding and communication, spatial awareness, learning and effectiveness as support tool. Based on the NASA TLX-scale questionnair results, mixed reality scored significantly lower under the “mental,” “temporal,” “performance,” and “frustration” categories compared to usual 2D. Conclusion: The integration of MR technology in orthopaedic surgery reduces the dependence on surgeons’ levels of experience and provides personalized 3D visualization models for accurate diagnosis and treatment of orthopaedic diseases. This integration is clearly one of the prominent future development directions in medical surgery.